Allosteric Regulation of Oligomerization by a B12 Trafficking G-Protein Is Corrupted in Methylmalonic Aciduria. Issue 7 (18th July 2019) - Ruetz, Markus; Campanello, Gregory C.; McDevitt, Liam; Yokom, Adam L.; Yadav, Pramod K.; Watkins, David; Rosenblatt, David S.; Ohi, Melanie D.; Southworth, Daniel R.; Banerjee, Ruma
Summary: Allosteric regulation of methylmalonyl-CoA mutase (MCM) by the G-protein chaperone CblA is transduced via three "switch" elements that gate the movement of the B12 cofactor to and from MCM. Mutations in CblA and MCM cause hereditary methylmalonic aciduria. Unlike the bacterial orthologs used previously to model disease-causing mutations, human MCM and CblA exhibit a complex pattern of regulation that involves interconverting oligomers, which are differentially sensitive to the presence of GTP versus GDP. Patient mutations in the switch III region of CblA perturb the nucleotide-sensitive distribution of the oligomeric complexes with MCM, leading to loss of regulated movement of B12 to and/or from MCM and explain the molecular mechanism of the resulting disease. Graphical Abstract: Highlights: Unlike the bacterial orthologs, human MCM-CblA form multiple oligomeric complexes Annular and linear MCM-CblA complexes are seen with GMPPCP and GDP, respectively Switch III mutations in CblA perturb the distribution of oligomeric complexes These CblA mutations also impair B12 loading and offloading leading to disease Abstract : Nucleotide-sensitive changes in oligomeric complexes between B12 -dependent methylmalonyl-CoA mutase and the trafficking GTPase CblA, distinguish them from their bacterial orthologs. Mutations in a signaling element in CblA impair the regulated distribution of these complexes, impact B12 loading/offloading function, and lead to disease.